The Effectiveness of School Principals in Managing School Operational Assistance (BOS) Funds - Siti Nurjannah; Risfa Tri Ulfa; Ngantori; Afriana Santosa (Journal of Educational Management Research, 2025)
This study aims to analyze the effectiveness of school principals’ work in managing the School Operational Assistance (BOS) funds. A qualitative descriptive approach was employed. The participants included school principals, BOS treasurers, and BOS management teams. Data were collected through in-depth interviews, observation, and document analysis, with data validity ensured through source and technique triangulation. The results indicate that principals’ effectiveness in managing BOS funds is reflected in their managerial functions, including planning, budgeting, and financial supervision. Principals actively ensure timely fund management, despite facing administrative and technical challenges. Budget planning is conducted based on real school needs and prioritized collaboratively with the BOS management team. Program development and budget allocation follow systematic procedures aligned with technical guidelines, and financial calculations are carried out rationally within the permissible limits. The study concludes that principals’ managerial competence—coordinating planning, setting priorities, managing time, and allocating funds accountably—determines the effectiveness of BOS fund management. The findings imply that strengthening principals’ managerial capacity is essential for enhancing the efficiency and accountability of school fund management.